Acute Renal Failure in Patients with Severe Falciparum Malaria: Using the WHO 2006 and RIFLE Criteria - Vipa Thanachartwet; Varunee Desakorn; Duangjai Sahassananda; Ko Ko Yazar Kyaw Win; Thanom Supaporn (International Journal of Nephrology)
There are limited data on the application of the RIFLE criteria among patients with severe malaria. This retrospective study was conducted by reviewing 257 medical records of adult hospitalized patients with severe falciparum malaria at the Mae Sot General Hospital, Tak province in the northern part of Thailand. The aims of this study were to determine the incidence of acute renal failure (ARF) in patients with severe falciparum malaria and its association with RRT as well as in-hospital mortality. Using the WHO 2006 criteria, ARF was the second most common complication with incidence of 44.7% (115 patients). The requirement for RRT was 45.2% (52 patients) and the in-hospital mortality was 31.9% (36 patients). Using the RIFLE criteria, 73.9% (190 patients) had acute kidney injury (AKI). The requirement for RRT was 11.6% (5 patients) in patients with RIFLE-I and 44.9% (48 patients) in patients with RIFLE-F. The in-hospital mortality gradually increased with the severity of AKI. The requirement for RRT (P<0.05) and the in-hospital mortality (P<0.05) were significantly higher in ARF patients with severe falciparum malaria using both criteria. In conclusion, the RIFLE criteria could be used for diagnosing AKI and predicting outcomes in patients with severe malaria similar to the WHO 2006 criteria.